2019
DOI: 10.1177/1559827619879694
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Origins of Health and Disease (DOHaD)

Abstract: For years many have believed that genetic heritage defined one’s destiny, if an individual would grow to be healthy, or if he or she would suffer from chronic illness or cancer. Recent scientific evidence and the field of epigenetics has proven this to be untrue. Certainly, the DNA sequence and the genetic code are fixed; but the field of epigenetics has shown how methylation and other chemical modifications of the genome directly influence the production of proteins that can alter the phenotype of an organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…On the other hand, according to the Developmental Origins of Health and Disease ( 51 ) hypothesis, most of the individual metabolic phenotypes are determined in utero. In particular, exposure to a hostile uterine environment has been associated—in humans and model organisms—with adult hyperphagia and late onset metabolic disorders, due to impaired placenta development and function ( 52 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, according to the Developmental Origins of Health and Disease ( 51 ) hypothesis, most of the individual metabolic phenotypes are determined in utero. In particular, exposure to a hostile uterine environment has been associated—in humans and model organisms—with adult hyperphagia and late onset metabolic disorders, due to impaired placenta development and function ( 52 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…This concept is based on Barker’s theory of the evolutionary origins of adult health and disease (DOHaD). This theory defines the relationship between early developmental influences on health and disease in adulthood and aging [ 52 54 ]. We observed that long-term programming was sex-dependent in both non-stressed and PRS aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genetic predisposition, environmental factors experienced during fetal life and childhood have been found to influence brain and nervous system functions through epigenetic changes. For example, the DOHaD theory (developmental origins of health and disease) has been proposed that inadequate nutrition during fetal life may lead to the risk of chronic diseases such as hypertension in adulthood [72]. It has also been pointed out that excess salt also may induce epigenetic saltsensitive hypertension [73].…”
Section: Epigenetics In Salt-sensitive Hypertensionmentioning
confidence: 99%